FROM DISCRIMINATION TOWARDS THE JUSTICE OF LAW (A STUDY OF MARRIAGE REGISTRATION FOR ADHERENT OF BELIEF): (A Study Of Marriage Registration For Adherent Of Belief) - Syarifa Khasna (Asian Journal of Law and Humanity, 2021)
The existence of adherents of belief in Indonesia is still discriminated against regardingtheir legal standing in the front of the State, especially regarding the issue of marriageregistration. Adherents of belief are not included in the religion recognized by the stateso that it is difficult to register their marriages. This is important to discuss becausemarriage registration will affect the marital legal standing and is related to the state'sobligation to provide justice and equal rights. This article discusses the legal justice ofmarriage registration for adherents of belief using the normative juridical method. Theresults of the study indicate that although the state has regulated the procedure forregistering marriages for adherents of belief, there are still many adherents of beliefwho experience problems in registering marriages because not all religiousorganizations are registered. This is phenomenon are deemed not in line with theimplementation of the 1945 Constitution which guarantees the constitutional rights ofadherents of belief, including the registration of marriages.